Prediction of mortality with unmeasured anions in critically ill patients on mechanical ventilation - Novović, Miloš N.; Jevdjić, Jasna (Vojnosanitetski pregled, 2014)
Background/Aim. Acid-base disorders are common within critically ill patients. Physicochemical approach described by Stewart and modified by Figge gives precise quantification method of metabolic acidosis and insight into its main mechanisms, as well as influence of unmeasured anion on metabolic acidosis. The aims of this study were to determine whether the conventional acid-base variables are connected with survival rate of critically ill patients at Intensive care unit; whether strong ion difference/strong ion gap (SID/SIG) is a better predictor of mortality rate comparing to conventional acid-base variables; to determine all significant predictable parameters for the 28-day mortality rate at intensive care units. Methods. This retrospective observational analytic study included 142 adult patients requiring mechanical ventilation, survivors (n = 68) and nonsurvivors (n = 74). Apparent strong ion difference (SIDapp), effective strong ion difference (SIDeff) and SIG values were calculated with the Stewart-Figge’s quantitative biophysical method. Descriptive and analytical statistical methods were used in the study [t-test, Mann-Whitney U test, χ2-test, binary logistic regression, Reciever operating characteristic (ROC) curves, calibration]. Results. Age, Na+, acute physiology and chronic health evaluation (APACHE II), Cl-, albumin, SIG, SID app, SIDeff, and aninon gap (AG) were statistically significant predictors. AG represented a model with imprecise calibration, i.e. a model with little predictive power. APACHE II had p-value more than 0.05 if it was near it, and therefore it could be considered potentially unreliable for outcome prediction. SIDeff and SIG represented models with well-defined calibration. ROC analysis results showed that APACHE II, Cl-, albumin, SIDeff, SIG i AG had the largest area bellow the curve. By creation of logistic models with calibration methods, we found that outcome depends on SIG and APACHE II score. Conclusion. Based on our data, unmeasured anions provide prediction of mortality of critically ill patients on mechanical ventilation, unlike the traditional acid-base variables which are not accurate predictors of the 28-day mortality rate.
Keywords: critical illness; acid-base imbalance; intensive care units; mortality